2017
DOI: 10.1590/1678-69712017/administracao.v18n4p109-136
|View full text |Cite
|
Sign up to set email alerts
|

Making a Career in a Male-Dominated Field: The Meaning of Work for Women Employed in the Financial Markets

Abstract: Este artigo pode ser copiado, distribuído, exibido, transmitido ou adaptado desde que citados, de forma clara e explícita, o nome da revista, a edição, o ano e as páginas nas quais o artigo foi publicado originalmente, mas sem sugerir que a RAM endosse a reutilização do artigo. Esse termo de licenciamento deve ser explicitado para os casos de reutilização ou distribuição para terceiros. Não é permitido o uso para fins comerciais. JULIANNA GRIPP SPINELLI-DE-SÁFaculdade CNEC de Rio das Ostras, Rio das Ostras -RJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
1
7
0
2
Order By: Relevance
“…According to Tolfo and Piccinini (2007), in the view of the MOW group, at the individual level the meaning of work can be defined as the social representation of the task performed by the individual, at the collective level by the feeling of belonging to a united class that carries out common work, and at the social level by the feeling of accomplishing work that contributes to society (Spinelli-De-Sá, Lemos, & Cavazotte, 2017). The adaptation made by Oliveira et al (2004) to the classification used by Morin (2001) highlights the meaning of work in the individual, organizational, and social dimensions.…”
Section: Work and The Meaning Of Workmentioning
confidence: 99%
“…According to Tolfo and Piccinini (2007), in the view of the MOW group, at the individual level the meaning of work can be defined as the social representation of the task performed by the individual, at the collective level by the feeling of belonging to a united class that carries out common work, and at the social level by the feeling of accomplishing work that contributes to society (Spinelli-De-Sá, Lemos, & Cavazotte, 2017). The adaptation made by Oliveira et al (2004) to the classification used by Morin (2001) highlights the meaning of work in the individual, organizational, and social dimensions.…”
Section: Work and The Meaning Of Workmentioning
confidence: 99%
“…Working abroad may also present various work difficulties to migrant workers, like adjusting to the host country, which may hinder one's work performance (Doki et al, 2018). The construction of the meaning of work difficulty can directly influence groups, such as work colleagues, leaders, and communities (Spinelli- De-Sá, 2017). They often undergo strenuous labor and experience boundaries in achieving their goals.…”
Section: Work Difficultiesmentioning
confidence: 99%
“…Taking this into account, many women encounter different challenges, especially in a demanding male work environment (Forkuor et al, 2020). Furthermore, recent studies have highlighted many difficulties that women still encounter in their professional day-to-day lives are most likely not experienced by men first hand (Andrade & Carvalho-Neto, 2015; Spinelli- De-Sá, 2017). This theme uses this to understand the challenges better and identify reasonable practices, strategies, and suggestions to support women's employment (Lekchiri&Kamm, 2020).…”
Section: Work Difficultiesmentioning
confidence: 99%
“…Simply put, it denotes a set of challenges for women that aspire to be leaders (Carli and Eagly, 2016). More recently, however, a study suggested that this perception is changing in such a way that women start to think that they have no limits anymore (Spinelli-de-Sá et al , 2017).…”
Section: Gender and Leadershipmentioning
confidence: 99%